The organizations of psychologists in Argentina and the kidnapping and disappearance of Beatriz Perosio, victim of state terrorism - Klappenbach, Hugo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
On August 8, 1978, Beatriz Perosio was kidnapped from the kindergarten where she worked in the Palermo neighborhood of Buenos Aires. At that time, Beatriz Perosio was President of the Association of Psychologists of Buenos Aires (APBA) and of the Federation of Psychologists of the Argentine Republic (FePRA), an institution that she herself had helped to organize a year earlier. The paper analyzes the actions carried out by the organizations of psychologists in the country after the kidnapping. To this end, it reconstructs the emergence and history of such organizations, especially the APBA, in which Perosio played a central role.